Quality of the Evidence Supporting the Role of Acupuncture for Stable Angina Pectoris: An Umbrella Review of Systematic Reviews - Shen, Min; Huang, Jinke; Qiu, Tao (Frontiers in Cardiovascular Medicine, 2021)
Background: An increasing number of systematic reviews/meta-analyses (SRs/MAs) of clinical trials have begun to investigate the effects of acupuncture for the treatment of stable angina pectoris (SAP). To systematically appraise and synthesize these results, we conducted an overview of SRs/MAs on acupuncture for SAP. Methods: Eight databases were searched ranging from their inception to December 2020. SRs/MAs of acupuncture for SAP were included. The methodological quality, and evidence quality were evaluated by the Assessing the Methodological Quality of Systematic Reviews 2 (AMSTAR-2), and Grading of Recommendations Assessment, Development and Evaluation (GRADE) system, respectively. Results: A total of seven published SRs/MAs that met the inclusion criteria were included in this overview. According to the evaluation results of AMSTAR-2, two studies were considered as moderate quality, and the remaining five were considered as very low quality. According to GRADE, a total of 18 outcome indicators extracted from included studies were evaluated. The evidence quality was very low in 3, low in 3, moderate in 8, and high in 4. Risk of bias was the most common downgrading factor in the included studies, followed by imprecision, inconsistency, publication bias, and indirectness. Conclusion: To conclude, acupuncture may be beneficial for SAP from the currently published evidence. Further rigorous, more normative and comprehensive SRs/MAs are required to provide robust evidence for definitive conclusions.